THE EFFECT OF CORPORATE GOVERNANCE AND CAPITAL STRUCTURE ON PERFORMANCE OF FIRMS LISTED AT THE EAST AFRICAN COMMUNITY SECURITIES EXCHANGE - Okiro, Kennedy; Aduda, Josiah; Omoro, Nixon (European Scientific Journal, ESJ, 2015)
The purpose of the study was to establish the effect of corporate governance and capital structure on performance of firms listed at the East African community securities exchange. Specifically the study sought to establish the effect of capital structure on the relationship between corporate governance and firm performance of listed companies in Kenya, Tanzania, Uganda, Rwanda and Burundi. Based on the agency theory this study builds a comprehensive framework to answer the research question on whether good corporate governance affects firms performance by integrating capital structure into the governance model. A census survey was carried out on all the 98 listed companies between 2009 and 2013 in Nairobi Securities Exchange, Uganda Securities Exchange, Dar es Salaam Stock Exchange and Rwanda Stock Exchange. Out of the 98 firms that were targeted, 56 were analyzed constituting 57%. The findings revealed that the there was a significant positive relationship between corporate governance and firm performance. The study also confirmed that there is a positive significant intervening effect of capital structure (leverage) on the relationship between corporate governance and firm performance. From a theoretical perspective, this study not only explains how corporate governance affects firm performance, but also uncovers the importance of capital structure in a corporate governance system.